Melek Investasi dan Pengelolaan Keuangan bagi Gen Z - Eindye Taufiq (Universitas Muria Kudus, 2024)
This community service is carried out to provide insight to Gen Z aged 12-27 years regarding financial management and investments that they need to make to have financial intelligence in facing a future full of uncertainty. This dedication will provide new insight for Gen Z on how they should view money and finances according to their generation and the obstacles that will occur according to their generation. Gen Z can have a secure and prosperous financial future by making investments and financial planning. Gen Z can overcome their financial obstacles and create a bright, sustainable future by realising the value of early investing and careful financial planning.